(untitled) (Journal of Bangladesh Institute of Planners, 2025)
The economic circumstance of Bangladesh is crucial for the attainment of its development objectives, as globalization has prompted apprehensions regarding regional development. Bangladesh, the second-largest economy in South Asia, is currently ranked 35th in nominal GDP and 25th in nominal GDP based on purchasing power parity. The country’s GDP increased by 5.82 percent in 2023-24, compared to 5.78 percent in 2022-23. The purpose of this investigation is to determine the formal regions of Bangladesh concerning their economic circumstances and to identify the factors that either promote or hinder economic development in different districts. The research was analysed across 64 districts using the Composite Weighted Index Method, which considered both economic and non-economic factors such as remittance inflow, literacy rate, solvency head count ratio (HCR), bank deposit, and employment rate. The study analysed key economic indicators such as employment, income, revenue, budget allocation, infrastructural development, educational opportunities, and healthcare facilities. It found a loop connectivity between government revenue, budget allocation, employment, and income across different districts, which is crucial for overall economic growth. This allows policymakers to more effectively allocate resources and to personalize interventions, thereby facilitating targeted efforts to stimulate economic growth. The findings can be a source of help for future policy decisions and contribute to the nation’s development objectives. JBIP, Vol. 17, 2024, pp. 119-136